2018
DOI: 10.1016/j.envint.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to polybrominated diphenyl ethers and predisposition to frustration at 7 months: Results from the MIREC study

Abstract: Prenatal exposure to PBDEs was associated with increased incidence of crying and screaming with delayed onset of discomfort movement, which may indicate a predisposition to frustration and lack of habituation in infants younger than 12 months from the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…An increasing number of studies have reported that newborn and fetal exposure to organochlorinated and/or brominated chemicals might have adverse effects on humans and wildlife. Prenatal exposure to PBDEs was associated with cognitive deficits and behavioral problems in children . Additionally, gestation period exposure to PBDEs would delay neuro ontogeny, alter motor activity, and reduce performance on learning and habituation tasks in mice .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have reported that newborn and fetal exposure to organochlorinated and/or brominated chemicals might have adverse effects on humans and wildlife. Prenatal exposure to PBDEs was associated with cognitive deficits and behavioral problems in children . Additionally, gestation period exposure to PBDEs would delay neuro ontogeny, alter motor activity, and reduce performance on learning and habituation tasks in mice .…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure to PBDEs was associated with cognitive deficits and behavioral problems in children. 74 Additionally, gestation period exposure to PBDEs would delay neuro ontogeny, alter motor activity, and reduce performance on learning and habituation tasks in mice. 75 Similarly, maternal exposure to high levels of contaminants may pose adverse effects to the calf dolphins, including endocrine disruption and neurotoxicity.…”
Section: Pbde Concentrations Inmentioning
confidence: 99%
“…Details about eligibility and exclusion criteria are outlined by Arbuckle et al 32 At age 36-48 months, a subset of 610 participating children in six cities were included in a follow-up study in which researchers assessed neurodevelopment. 3,[34][35][36] We restricted our study to 517 mother-child pairs from this group based on the availability of biomarkers and intelligence quotient (IQ) scores. 33,35,36 The MIREC study received ethics approval from Health Canada and the Institutional Review Board of CHU Sainte-Justine Research Centre, as well as all recruitment centers.…”
Section: Study Participantsmentioning
confidence: 99%
“…Plusieurs études de cohortes mère-enfant traitant du lien entre l'exposition aux PBDE qui débute in utero et les troubles du neurodéveloppement ont été publiées depuis 2009 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) dans différents pays (Europe, Chine, Etats-Unis, Canada). Elles sont présentées dans le tableau 1.…”
Section: Données éPidémiologiquesunclassified